Role of NBC1 in apical and basolateral [Formula: see text] permeabilities and transendothelial [Formula: see text] fluxes in bovine corneal endothelium - Li, Jinhua (2004)
Corneal transparency and hydration control are dependent on [Formula: see text] transport properties of the corneal endothelium. Recent work (13) suggested the presence of an apical [Formula: see text] cotransporter (NBC1) in addition to a basolateral [Formula: see text] cotransporter. We examined whether the NBC1 cotransporter contributes significantly to basolateral or apical [Formula: see text] permeability and whether the cotransporter participates in transendothelial net [Formula: see text] flux in cultured bovine corneal endothelium. NBC1 protein expression was reduced using small interfering RNA (siRNA). Immunoblot analysis showed that 5–15 nM siRNA decreased NBC1 expression by 80–95%, 4 days posttransfection. Apical and basolateral [Formula: see text] permeabilities were determined by measuring the rate of pH(i) change when [Formula: see text] was removed from the bath under constant pH or constant CO(2) conditions. Using either protocol, we found that cultures treated with NBC1 siRNA had sixfold lower basolateral [Formula: see text] permeability than untreated or siCONTROL siRNA-treated cells. Apical [Formula: see text] permeability was unaffected by NBC1 siRNA treatment. Net non-steady-state [Formula: see text] flux was 0.707 ± 0.009 mM·min(−1)·cm(2) in the basolateral-to-apical direction and increased to 1.74 ± 0.15 when cells were stimulated with 2 μM forskolin. Treatment with 5 nM siRNA decreased basolateral-to-apical flux by 67%, whereas apical-to-basolateral flux was unaffected, significantly decreasing net [Formula: see text] flux to 0.236 ± 0.002. NBC1 siRNA treatment or 100 μM ouabain also eliminated steady-state [Formula: see text] flux, as measured by apical compartment alkalinization. Collectively, reduced basolateral [Formula: see text] permeability, basolateral-to-apical fluxes, and net [Formula: see text] flux as a result of reduced expression of NBC1 indicate that NBC1 plays a key role in transendothelial [Formula: see text] flux and is functional only at the basolateral membrane.